2021
DOI: 10.52131/pjhss.2021.0902.0129
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Performance of Small & Medium Enterprises: The Mediating Role of Knowledge Management

Abstract: Entrepreneurial orientation, entrepreneurial innovation, and knowledge management all play critical roles in improving the performance of Pakistan's small and medium-sized enterprises (SMEs). Pakistan's business index score decreased from 137th to 138th due to the country's low performance in the small and medium-sized enterprise sector. Small and medium-sized firms must overcome several obstacles in order for the country's economy to thrive. This study will address this issue. We used a cross-sectional design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
3
13
0
1
Order By: Relevance
“…The major goal of the study was to establish whether there is a link between green (human resource management) practises and employee performance in small and mediumsized enterprises (SMEs) in Pakistan. The findings are consistent with prior study, which revealed that green HR practises have a substantial impact on employee commitment and satisfaction, which in turn leads to improved employee performance (Khan, Tufail & Ali, 2021). In addition, if the employees' green behaviour is taken into consideration throughout the recruiting process, it is more likely that the employees will exhibit green behaviour after being hired.…”
Section: Discussionsupporting
confidence: 90%
“…The major goal of the study was to establish whether there is a link between green (human resource management) practises and employee performance in small and mediumsized enterprises (SMEs) in Pakistan. The findings are consistent with prior study, which revealed that green HR practises have a substantial impact on employee commitment and satisfaction, which in turn leads to improved employee performance (Khan, Tufail & Ali, 2021). In addition, if the employees' green behaviour is taken into consideration throughout the recruiting process, it is more likely that the employees will exhibit green behaviour after being hired.…”
Section: Discussionsupporting
confidence: 90%
“…Accurate and reliable data is essential to monitor and evaluate the performance and effectiveness of any institution and system (A. J. Khan & Iqbal, 2020;A. J. Khan, Tufail, & Ali, 2021).…”
Section: Lack Of Reliable Data and Informationmentioning
confidence: 99%
“…Organizations must assess their information technology competencies regularly to retain their competitive advantage in the market (Peppard, Lambert, & Edwards, 2000). Information technologies help organizations to achieve competitive advantage in terms of innovation, quality, customer satisfaction, customer retention, employees commitment (Junaid, Bashir, Nasim, & Ahmad, 2021) and reduction of operating cost; and in turn, use these competitive advantages to increase organizational performance (Khan, Tufail, & Ali, 2021) that ultimately leads towards better financial performance.…”
Section: Mediating Role Of Organizational Performancementioning
confidence: 99%